(untitled) (Bangladesh Veterinarian, 2024)
Microbial contamination of drinking water poses a health threat for man and animals. The aim of this study was to detect Escherichia coli (E. Coli) and Salmonella in drinking water from the Sher-e-Bangla Agricultural University (SrAU) campus and its surrounding areas between January 2021 and August 2021. A total of 60 water samples were collected from dormitories, academic buildings and nearby shopping centres. Identification of bacteria was done using growth characteristics on selective media, staining, microscopic examination, and biochemical tests. The overall prevalence of contamination was 53.3%, with the highest rate (61.1%) in water from shopping centres. Drinking water in the SrAU campus and its vicinity is unsafe for drinking and household purposes. Sanitation programmes of the SrAU health centre need to be strengthen to mitigate health risks of the community. Bang. vet. 2024. Vol. 41, No. 1 – 2, 1 – 6